2003
DOI: 10.1093/humrep/deg337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin in the prevention of post-operative adhesion formation in a rat uterine horn adhesion model

Abstract: This study showed that even single dose ME therapy was effective in the prevention of post- operative i.p. adhesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…In open surgery, ROS scavengers have been described as reducing adhesion formation in mice [45], rats [39,40,[42][43][44], and rabbits [41], but the effect is not consistent (e.g., vitamin E failed to decrease adhesion formation in rats) [90]. In our laparoscopic mouse model, we confirmed that ROS scavengers can decrease adhesion formation, although the overall effect was small.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In open surgery, ROS scavengers have been described as reducing adhesion formation in mice [45], rats [39,40,[42][43][44], and rabbits [41], but the effect is not consistent (e.g., vitamin E failed to decrease adhesion formation in rats) [90]. In our laparoscopic mouse model, we confirmed that ROS scavengers can decrease adhesion formation, although the overall effect was small.…”
Section: Discussionsupporting
confidence: 64%
“…In rats the same dose of SOD and catalase (i.e., 15,000 U/kg IV) decreased intraperitoneal adhesions [39]. Also for melatonin, the same IP dose of 10 mg/kg body weight was effective in rats [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of steroidal [8][9][10][11] and non-steroidal anti-inflammatory compounds [12][13][14][15][16] have been tested, as well as agents that interfere with specific cytokines [17] or vascular permeability [18], chemotherapeutic agents [19] and immunosuppressive drugs [20]. In a related vein, many agents that scavenge the free radicals generated by inflammation have been tested [21,22].…”
Section: Pharmacological Approaches To Preventing Peritoneal Adhesionsmentioning
confidence: 99%